Identification of a novel SGCA missense mutation in a case of limb‐girdle muscular dystrophy 2D with the absence of four sarcoglycan proteins. Issue 3 (15th April 2019) - Lu, Yanpeng; Song, Xueqin; Ji, Guang; Wu, Hongran; Li, Duan; Sun, Shuyan
Abstract : Limb‐girdle muscular dystrophy 2D (LGMD2D) is caused by mutations in the α‐sarcoglycan gene ( SGCA ). Due to lack of specificity, it is impossible to identify LGMD2D only by clinical symptoms and conventional immunohistochemical staining. The loss of any protein (α‐, β‐, γ‐, δ‐sarcoglycan) that represent sarcoglycanopathy may cause reduction or absence of the other three proteins. Here, we report a patient with a complete loss of all the four proteins. Next generation sequencing (NGS) results showed a missense mutation (C.218 C > T) and a partial heterozygous deletion containing exons 7 and 8 of SGCA, which led to the final diagnosis of the patient. The discovery of this new mutation could broaden the spectrum of SGCA mutations, which may be associated with putative LGMD2D, especially when all the four proteins are completely missing.